The impact of self-regulated learning strategies on academic performance for online learning during COVID-19 - Xu, Ling; Duan, Peng; Padua, Shirley A.; Li, Chengyou (Frontiers in Psychology, 2022)
The COVID-19 pandemic led higher education institutions to transition to online learning. The present study was designed to investigate students’ self-regulated learning strategies on academic performance in online learning. We analyzed the differences in college students’ self-regulated learning (SRL) strategies according to their grade point average (GPA). The study included 1163 students at a distance education university in China. Two online questionnaires were used to determine online SRL strategies. GPA scores were obtained from the university exam database to determine academic performance. The analysis showed that there are great differences between different self-regulated strategies and between different students when accepting the online learning. The analysis also showed that self-evaluation, metacognitive self-regulation, and effort regulation were positive predictors of academic progress, besides, self-evaluation and effort regulation had mutual influence effect on the improvement of GPA in online learning. These data will help teachers, education policymakers, and education administrators adopt and implement online learning services to improve students’ academic performance.